Simulation Analysis Impact of Transaction Cost on Economic Behavior of Cattle-Coconut Farmersâ Household in Bolaang Mongondow - Elly, FH; Sinaga, BM; Kuntjoro, SU; Kusnadi, N (ANIMAL PRODUCTION, 2012)
Beef cattle farming in Bolaang Mongondow are the source of household income which is in fact still run traditionally and hiring family members. The problem faced is the price received by the farmers is less than the selling price minus transaction cost. This research aimed to analyze the impact of transaction cost, input and output prices on economic behavior of cattle-coconut farmersâ household. This research applied survey method and the collected data were data cross section and data time series. Purposive sampling and simple random sampling were used to determine the research location and respondents (233 households), respectively. Â Data analysis was simulation analysis using SAS 9.0 program, served in 6 scenarios with combination of transaction cost, output price, input price and wage. Model validation was done prior to the simulation to find the correct model. The result showed that the model applicable for long term was scenario 4. Â Broker cost, copra shipping cost combined with output price also decline of cow shipping cost, administration cost, retribution and copra shipping cost combined with output price gave significant impact towards income and welfare of cattle-coconut farmersâ household in Bolaang Mongondow.Â Keywords: simulation analysis, transaction cost, beef cattle farming, coconutÂ Animal Production 14(2):123-131